Investigation of wind and sound field characteristics of multi-rotor unmanned aerial vehicle. (July 2020) - Cao, Huiru; Cheng, Haixiu; Zhu, Wenjian
Wind field and sound field characteristics are the key indexes for unmanned aerial vehicle. Therefore, in this study, the wind field and sound field characteristics of a quad-rotor unmanned aerial vehicle are investigated. First, the experimental platform was set up based on quad-rotor unmanned aerial vehicle. Second, the experiments were performed on the wind field and the sound field characteristics of the unmanned aerial vehicle at different working currents. Then, the experiment results were analysed. Meanwhile, the experimental results showed that the working current has a large impact on the wind field and the wind intensity increases as working current increases; as the working current increases, the sound field is enhanced and a linear relationship exists; within a certain distance range of the unmanned aerial vehicle, as distance increases, sound intensity dramatically decreases. The presented methods and results can not only be used to evaluate the performance of the electric multi-rotor unmanned aerial vehicle but also provide references for the further improvement of the performance of the unmanned aerial vehicle.